ORIENTALISM AND POST-COLONIAL READING OF THE U.S. POLICY TOWARD INDONESIA DURING NIXON ADMINISTRATION - Wardaya, Baskara T. (International Journal of Humanity Studies (IJHS), 2021)
Abstract            Through the examination of documents pertaining to the United States policies toward Indonesia, this paper studies how Washington viewed Indonesia almost three decades after colonialism had been officially over. More specifically, this paper studies U.S. assistance programs provided for Indonesia during the administration of President Richard M. Nixon. By using the perspective of postcolonial studies on international relations, it shows that while on the surface the assistance programs of the Nixon administration appeared to be altruistic and helpful, a deeper look at them shows that the programs were imbued with subliminal Eurocentric liberal international theory of international relations.             It further shows that the administration’s programs were not only self-serving, but were also implemented with an orientalist spirit by the United States as part of the “superior” West over Indonesia that was considered part of the East and therefore was “inferior” and in need of help from the West. In light of Edward Said’s postcolonial studies of West and East relations, the policies clearly reflect orientalist views and practices, even long after colonialism formally ended. Keywords: Orientalism, English School Theory, Neoliberal International Theory, the Nixon administration, Indonesia